Retrieval of parameters of few-cycle laser pulses from high-energy photoelectron spectra of atoms by a genetic algorithm - Zhou, Zhaoyan; Wang, Xu; Chen, Zhangjin; Lin, C. D. (My University, 2017)
According to the quantitative rescattering theory, the laser features are imbedded in the returning electron wave packets. By analyzing high-energy photoelectron wave packets on the two sides of the linearly polarization axis we can retrieve the experimental laser pulse irrespective of the atomic targets. Laser parameters including its carrier-envelope phase, pulse duration, and peak intensity can be retrieved within a small range simultaneously from the output of the genetic algorithm. This is a simple direct retrieval method for characterizing a phase-stabilized few-cycle laser pulse based only on one set of photoelectron spectra.